Joint effect of magnesium and yttrium on enhancing thermoelectric properties of n-type Zintl Mg3+δY0.02Sb1.5Bi0.5 - Song, S. W.; Mao, J.; Bordelon, Mitchell; He, Ran; Wang, Y. M.; Shuai, Jing; Sun, J. Y.; Lei, X. B.; Ren, Z. S.; Chen, S.; Wilson, S.; Nielsch, Kornelius; et al. (Materials Today Physics, 2019)
N-type Mg3Sb2-based Zintl compounds have attracted considerable interest in recent years for their high thermoelectric performance. Mg3Sb2-based compounds inherently have p-type transport properties because of the presence of intrinsic Mg vacancies. Therefore, eliminating Mg vacancies and increasing the electron concentration are crucial for achieving high-performance n-type Mg3Sb2-based materials. The addition of excess Mg in the initial composition and the doping of chalcogens (Te, Se, and S) at the Sb site have been the primary methods used to date. Here, we demonstrate that n-type conduction was successfully achieved by a simple Y doping at the Mg site without adding extra Mg in the initial composition. Neutron diffraction analysis shows that Y preferentially goes to the Mg (Ⅱ) site and that almost all of the Mg vacancies are eliminated, giving rise to a strong donor effect to create n-type conduction. By eliminating the vacancies, the carrier concentration is easily optimized through the combination of Y and Mg, leading to a peak ZT of ∼1.8 at 773 K in Mg3.02Y0.02Sb1.5Bi0.5.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Carrier concentration; Mg vacancies; n-type Mg; Y doping